Inhibition of Transfer to Secondary Receptors by Heparan Sulfate-Binding Drug or Antibody Induces Noninfectious Uptake of Human Papillomavirus - Selinka, Hans-Christoph (American Society for Microbiology, 2007)
Infection with various human papillomaviruses (HPVs) induces cervical cancers. Cell surface heparan sulfates (HS) have been shown to serve as primary attachment receptors, and molecules with structural similarity to cell surface HS, like heparin, function as competitive inhibitors of HPV infection. Here we demonstrate that the N,N′-bisheteryl derivative of dispirotripiperazine, DSTP27, efficiently blocks papillomavirus infection by binding to HS moieties, with 50% inhibitory doses of up to 0.4 μg/ml. In contrast to short-term inhibitory effects of heparin, pretreatment of cells with DSTP27 significantly reduced HPV infection for more than 30 h. Using DSTP27 and heparinase, we furthermore demonstrate that HS moieties, rather than laminin 5, present in the extracellular matrix (ECM) secreted by keratinocytes are essential for infectious transfer of ECM-bound virions to cells. Prior binding to ECM components, especially HS, partially alleviated the requirement for cell surface HS. DSTP27 blocks infection by cell-bound virions by feeding into a noninfectious entry pathway. Under these conditions, virus colocalized with HS moieties in endocytic vesicles. Similarly, postattachment treatment of cells with heparinase, cytochalasin D, or neutralizing antibodies resulted in uptake of virions without infection, indicating that deviation into a noninfectious entry pathway is a major mode of postattachment neutralization. In untreated cells, initial colocalization of virions with HS on the cell surface and in endocytic vesicles was lost with time. Our data suggest that initial attachment of HPV to HS proteoglycans (HSPGs) must be followed by secondary interaction with additional HS side chains and transfer to a non-HSPG receptor for successful infection.